SELLING IN SECONDS: A PHENOMENOLOGICAL EXPLORATION OF SHORT VIDEO MARKETING ON INSTAGRAM REELS IN ENTREPRENEURIAL VENTURES - Gautama Sastra Waskita; Denny Rakhmad Widi Ashari, Akhmad Rifa’I, Mohammad Basid Al Haris (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The growing prominence of short video content in digital marketing highlights its potential as a powerful tool for entrepreneurial ventures to engage audiences and drive business outcomes. However, limited research explores how entrepreneurs navigate the unique affordances of platforms like Instagram Reels, particularly in resource-constrained environments. This study aims to investigate the role of short video marketing in entrepreneurial ventures by employing a qualitative phenomenological approach. Data were collected through in-depth interviews with entrepreneurs and analysed thematically to uncover key insights. The findings reveal three dominant themes: creativity and storytelling, strategic resource allocation, and audience engagement dynamics. Entrepreneurs utilized platform-specific features, such as algorithmic amplification and built-in editing tools, to craft compelling narratives and maximize marketing impact. Despite challenges such as algorithm variability, short videos emerged as cost-effective, accessible tools for enhancing brand visibility and consumer interaction. These results contribute to the theoretical discourse on platform affordances and entrepreneurial marketing while providing practical strategies for entrepreneurs to optimize their digital marketing efforts. The study underscores the need for future research on cross-platform dynamics, cultural variations, and the integration of emerging technologies. Implications for entrepreneurship training and policymaking highlight the critical role of short video marketing in shaping the future of digital entrepreneurship.